Influence of Counterion on Thermal, Viscoelastic, and Ion Conductive Properties of Phosphonium Ionenes. Issue 1 (August 2014) - Abdulahad, Asem I.; Jangu, Chainika; Hemp, Sean T.; Long, Timothy E.; Duchet‐Rumeau, Jannick; Gérard, Jean‐François; Galli, Giancarlo
Summary Anion metathesis enabled a systematic study focused on the thermal, viscoelastic, and conductivity properties of a 4P, 12 phosphonium ionenes with various counterions. Aqueous size exclusion chromatography confirmed the well‐defined synthesis of 4P, 12‐Br from the step‐growth polymerization of 1, 4‐bis(diphenylphosphino) butane and 1, 12‐dibromododecane at a 1:1 stoichiometric ratio. Subsequent anion‐exchange employing a dialysis method exchanged the Br‐ counterion to trifluoromethanesulfonate (TfO‐), bis(trifluoromethane) sulfonimide (Tf2N‐), and tetrafluoroborate (BF4‐) counterion. 1H nuclear magnetic resonance spectroscopy of the 4P, 12 ionenes showed a distinct upfield chemical shift for methylene protons adjacent to the phosphonium cation after anion‐exchange. Thermal characterization using thermogravimetric analysis and differential scanning calorimetry probed the thermal properties of the phosphonium ionenes. Counterion exchange to more bulky and delocalized anions led to improved thermal stabilities and lower glass transition temperatures. Rheological characterization facilitated the generation of time‐temperature superposition (TTSp) master curves and pseudo‐master curves for each 4P, 12 ionene. TTSp revealed two distinct relaxation modes attributed to long‐range segmental motion and electrostatic interactions. Anion‐exchange resulted in a shift of these two modes of relaxation to higher shear rates. The calculated melt flow activation energy and thermal expansion coefficients were also observed to decrease and increase, respectively. Melt rheological characterization also probed the temperature dependence of the storage and loss moduli and suggested that the counterions have a plasticizing effect on the viscoelasticity of the 4P, 12 ionene. Ionic conductivity increased with increasing size of the counterion (Br‐ < BF4‐< TfO‐< Tf2N‐) and demonstrated the viability of these novel materials as potential anion‐exchange ionomeric membranes.